Effects of immigration on the prevalence of malaria in rural areas of the Amazon basin of Brazil - Macgreevy, Patrick B. (1989)
Epidemiological studies were conducted on malaria in three rural areas of the Amazon basin in the State of Rondônia: the town of Costa Marques, Forte Príncipe da Beira (Fort), and an immigrant settlement in the nearby forest. These studies were instituted to document the malaria problem and to describe the role of immigration on its distribution and prevalence. Hospital records in the town show that the number of malaria cases increased five fold from 1983 to 1987 and that the predominant malaria parasite changel from Plasmodium vivax to P. falciparum. Increased malaria followed increased immigration and colonization of the forest. A series of epidemiologic studies suggested the linkage between malaria and immigration as the prevalence of malaria was 1-2% at the Fort, a stable community, 8-9% at Costa Marques, a growing community, and 14-26% in the new settlements in the forest.